RECONSTRUCTION OF THE HINDU RELIGIOUS EDUCATION LEARNING MODEL AT SD NEGERI 7 AND SD NEGERI 10 PEDUNGAN - Indiani, Ni Made; Dewa Sudyana; Ida Ayu Gde Yadnyawati (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
Hindu Religious and Character Education learning in elementary schools is still predominantly teacher-centered and cognitively oriented, resulting in limited internalization of Hindu values in students’ attitudes and behavior. This study aims to reconstruct a contextual, participatory, and value-based learning model and examine its implications for teacher performance and student learning outcomes. A qualitative approach with a multi-site design was employed using Participatory Action Research in two public elementary schools in Denpasar. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed descriptively through data condensation, data display, and reflective conclusion drawing. The findings indicate that the reconstruction process produced a Contextual–Participatory–Value-Based Learning model integrated with Discovery Learning and Reflective Pedagogy. Implementation of the model enhanced teachers’ ability to design value-oriented instruction, manage participatory learning activities, and apply authentic assessment, while also improving students’ cognitive, affective, and psychomotor learning outcomes, particularly in the internalization and practice of Hindu values. Keywords: Hindu Religious Education, Learning Reconstruction, Value-Based Learning, Character Education, Independent Curriculum, Local Wisdom.